2010
DOI: 10.1111/j.1365-2516.2009.02189.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of disease and adherence in adult patients with haemophilia

Abstract: Patients with moderate and severe haemophilia are evaluated on a regular basis at their haemophilia centres but patients with mild haemophilia are seen less often because of fewer problems related to their disease. The needs of patients with milder forms of haemophilia, however, are often underestimated, both by the patient and staff at healthcare facilities. This study evaluated the knowledge of disease and adherence to treatment among patients with severe, moderate and mild haemophilia. This was a prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 5 publications
5
35
0
Order By: Relevance
“…Studies of young people and adults with haemophilia have shown that 69% of patients aged 13-25 years [21] and 96% of patients aged over 25 [22] were aware of heredity i.e. a healthy son and carrier daughter.…”
Section: Discussionmentioning
confidence: 98%
“…Studies of young people and adults with haemophilia have shown that 69% of patients aged 13-25 years [21] and 96% of patients aged over 25 [22] were aware of heredity i.e. a healthy son and carrier daughter.…”
Section: Discussionmentioning
confidence: 98%
“…Brodin et al also found that middle‐aged patients expressed better adaptation than younger patients. Another variable to take into account is the perception and attitude towards the disease; some authors point out how patients with moderate or mild forms of haemophilia show poorer coping strategies than in severe forms due to the lack of experience and knowledge of symptoms …”
Section: Discussionmentioning
confidence: 99%
“…instructions and effectiveness) [3,48,92,93], perceptions of one's ability to influence health outcomes [94] and confidence in one's ability to meet the specific demands of cancer treatment and recovery [95], are all cognitive and motivational processes with the potential to influence treatment adherence. For example, patients are often not aware of the therapeutic effects of potentially lifesaving treatment which they are prescribed [79]. Decision-making competence [96] and patient involvement in decision-making [97], along with faith in the treatment option and physician [39], are additional barriers to adherence.…”
Section: Adolescents and Young Adultsmentioning
confidence: 99%
“…Disease severity [79] and complications [80], along with adverse clinical experiences [76], have a negative impact on adherence.…”
Section: Adolescents and Young Adultsmentioning
confidence: 99%